PENGARUH KUALITAS LAPORAN KEUANGAN, KONSERVATISMA AKUNTANSI DAN DEBT MATURITY PADA EFISIENSI INVESTASI - Anete Widowati; Lodovicus Lasdi (Universitas Katolik Widya Mandala Surabaya, 2021)
Companies in running their business will seek small financing to obtain greater profits. Investment efficiency is one of the company's efforts to achieve this goal. There are several factors that can affect investment efficiency such as the quality of financial statements, accounting conservatism, debt maturity and company size. In this study, investment efficiency is carried out using the regression equation between investment and sales development. For the success of the research, the selected object is a manufacturing company that has been listed on the IDX with a period spanning 2015-2018. Samples were selected through purposive sampling as many as 40 of 150 companies. The sample results were analyzed using multiple linear analysis methods. The results of the study show that the two financial statements have no effect on investment efficiency, but debt maturity has a significant positive effect on investment efficiency.